The impacts of partial replacement of red and processed meat with legumes or cereals on protein and amino acid intakes: a modelling study in the Finnish adult population - Meri Simojoki; Satu Männistö; Heli Tapanainen; Mirkka Maukonen; Liisa M. Valsta; Suvi T. Itkonen; Anne-Maria Pajari; Niina E. Kaartinen (Annals of Medicine, 2023)
AbstractBackground A shift towards more plant-based diets is considered healthy and environmentally sustainable but may cause a concern regarding protein and amino acid intakes. This modelling study aimed to assess the impacts of partial replacement of red and processed meat with legumes or cereals on the protein and indispensable amino acid intakes in the Finnish adult population.Materials and methods We used the cross-sectional data of the National FinDiet 2017 Survey (two non-consecutive 24-h recalls, n = 1655, 47% men, aged 18–74 years). Six replacement scenarios were created in which the amount of red and processed meat exceeding 70 g/day (Finnish nutrition recommendation), or 30 g/day (EAT-Lancet recommendation) was replaced with the same amounts of legumes, cereals or their combination. Differences to the reference diet were evaluated based on non-overlapping 95% confidence intervals. Population shares (%) below estimated average requirements (EAR) were calculated using the usual intake modelling methodology (SPADE).Results The replacement scenarios decreased the protein and indispensable amino acid intakes depending on gender and age. At the 70-g level, decreases were observed only in men aged 18–64 years. At the 30-g level, decreases were observed in other gender and age groups except women aged 65–74 years. In the scenarios, the mean daily protein intake was 15–18% of total energy intake (E%) (reference 17–18 E%), and the proportions below the EAR were 7–10% in men and 8–10% in women aged 18–64 years (reference 5–7%) and 20–25% in men and 16–20% in women aged 65–74 years (reference 14–17%). For total indispensable amino acids, the proportions below the EAR were <5% in the reference diet and the scenarios.Conclusions The mean daily protein intake remained sufficient when red and processed meat was partially replaced with legumes or cereals in the Finnish adult population. However, protein adequacy in the elderly population warrants attention and more research.